Reduced interferon-γ release in patients recovered from Legionnaires' disease. Issue 1 (1st January 2003) - Lettinga, K D; Weijer, S; Speelman, P; Prins, J M; van der Poll, T; Verbon, A
Abstract : Background: Legionella pneumophila, a Gram negative intracellular pathogen, causes Legionnaires' disease (LD). Interferon (IFN)-γ is important for host defence against L pneumophila so reduced IFN-γ production capacity and/or responsiveness might render humans more susceptible to infection with L pneumophila . Methods: Seventy seven patients who suffered from LD after a point source outbreak one year earlier participated in the study. Whole blood was incubated with non-specific stimuli (lipopolysaccharide (LPS) or interleukin (IL)-12) or specific stimuli (viable or heat killed L pneumophila ) to evaluate IFN-γ production, and with IFN-γ to evaluate IFN-γ responsiveness. Expression of complement receptor 3 on monocytes was determined by flow cytometry. Thirty seven companions who were also exposed but had not developed LD served as controls. Results: Patients released less IFN-γ than controls in response to stimulation with LPS (mean (SE) 393 (58) pg/ml v 914 (178) pg/ml; p=0.001) and IL-12 (96 (14) pg/ml v 177 (41) pg/ml; p=0.058). IFN-γ responsiveness, measured by release of IFN-γ inducible protein (IP)-10, tumour necrosis factor α, IL-12 production capacity, and monocyte expression of complement receptor 3, did not differ between patients and controls. IFN-γ release after stimulation with LPS and IP-10 release after stimulation with IFN-γ were weakly associated with severity of LD in the former patient group (ρ=–0.3, p=0.011 and ρ=–0.3, p=0.037, respectively). Conclusion: These results suggest that impaired IFN-γ production may contribute to susceptibility to L pneumophila infection.